2005
DOI: 10.1007/s11746-005-1071-8
|View full text |Cite
|
Sign up to set email alerts
|

In situ monitoring of solid fat content by means of pulsed nuclear magnetic resonance spectrometry and ultrasonics

Abstract: An ultrasonic technique was developed to study the crystallization process of edible fats on-line. A chirp wave was used instead of the conventional pulser signal, thus achieving a higher signal-to-noise ratio. This enabled measurements to be made in concentrated systems [~20% solid fat content (SFC)] through a 8.11-cm thick sample without significant signal loss. Fat samples were crystallized at 20, 25, and 30°C at a constant agitation rate of 400 rpm for 90 min. The crystallization process was followed by ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…Ultrasonic technology, on the other hand, proved to be an accurate technique to measure SFC on-line since no corrections needed to be made. Previous data (1) showed that this technique can be used even for high SFC values and that measurements do not depend on sample motion. Transducers can be placed in the pipe walls where the fat is being crystallized, and therefore the crystallization process can be followed in real time.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ultrasonic technology, on the other hand, proved to be an accurate technique to measure SFC on-line since no corrections needed to be made. Previous data (1) showed that this technique can be used even for high SFC values and that measurements do not depend on sample motion. Transducers can be placed in the pipe walls where the fat is being crystallized, and therefore the crystallization process can be followed in real time.…”
Section: Resultsmentioning
confidence: 99%
“…SFC was measured on-line by means of an ultrasonic technology developed previously in our laboratory (1,2). Figure 5 shows the comparison between the SFC obtained by the mq20, NMR-MOUSE, and ultrasonic technology for both samples (A and B) diluted 50% with canola oil and crystallized at 30°C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations